Analisis Kelayakan Finansial Penggantian Lini Manual Menjadi Lini Otomatis Produk Refrigerator Switch di PT. MM - Andira Andira; Astika Arisnawati (President University, 2018)
Sales data of FY10 to FY 15 shows increasing of switch D-1 demand. In fulfilling the demand, budget of production have been allocated by the head company. In fact, there is gap between the budget and cost required by production department. The condition cause the capacity lower than the demand. It happened to FY16. The problem should be solved because it has bad impact to customer satisfaction. Based on the problem identification, the problem of lack of budget can caused by the wrong estimation of demand. Refer to that problem, company decide to find out the better method in forecasting of demand and assume that the mother company will determine the suitable number of budget to produce as much as demand. Several methods of forecasting have been considered and trend liner method is the best method for the company demand pattern. Lack of capacity at FY16 before will require the increasing of capacity in several next periods. Changing the manual line to be automation line is an alternative to overcome the capacity problem. The result of analysis is automation line is more efficient than manual line. It reduced the number of operator from 7 to 4 per line. Adding one automation line need 3 years to get payback with net present value 249,377.88, internal rate of return is 18.93% and profitability is index 1.62Keywords: Payback Period, Net Present Value, Internal Rate of Return, Profitability Index